IMPLEMENTASI METODE BERKISAH DALAM MENUMBUHKAN MINAT BELAJAR SANTRI DI MADRASAH DINIYAH â€œAR-ROHMANâ€ Dsn. LOBANG, MLILIR, DOLOPO, MADIUN - Fitri Hanifah, Diah; Heriyudanta, Muhammad (Al-Lubab : Jurnal Penelitian Pendidikan dan Keagamaan Islam, 2022)
Interest is interested or fully visible with an activity because it realizes the importance of the activity. Students' lack of interest in learning, especially in the learning process, can result in students not understanding and remembering the subject matter presented by the teacher. One of the efforts that can be done is through the application of the storytelling method. The research method used is qualitative and the data collection method uses observation, interviews, documentation. This research resulted in the implementation of the storytelling method at Madrasah Diniyah Ar-Rohman aimed at fostering student interest in learning. The application of this storytelling method is carried out on Monday-Thursday. Meanwhile, on Fridays every 2/3 weeks. The storytelling method conveyed by the teacher uses two ways, namely direct storytelling and role playing. The implication of the application of the storytelling method at Madrasah Diniyah Ar-Rohman is that the students are very enthusiastic because, by using the storytelling method, the students pay more attention to the stories presented are interesting, so it fosters interest in learning. Barriers for teachers in the application of the storytelling method are the lack of vocabulary and understanding of the content of the stories conveyed, the teacher's lack of experience in teaching, the teacher's lack of confidence. Meanwhile, the obstacles for students are the different abilities of each student, the large number of students who are difficult to regulate, and inadequate environmental conditions.Keywords: Implementation, Storytelling Method, Interest in Learning